Analisis Kesalahan Berbahasa Mandarin Mahasiswa Tingkat Akhir di Salah Satu Universitas di Jawa Barat - Diana C. Sahertian (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2016)
It is important to do analysis on errors made by L2 learners. First, it is aimed at finding out why they made errors. Second, it is useful for teachers to know what errors the learners made. Third, it is possible that making errors may actually help learners to learn when they self-correct the errors they made (Ellis, 2000 :15). After learning Chinese language for seven semesters, the learners from one of universities in West Java still also made language errors. This article discusses the type of errors the learners made according to linguistics category taxonomy, surface strategy taxonomy, and communicative effect taxonomy, and the factors that cause those errors. The subjects of this research are the seven semester students learning Chinese language at one of universities in West Java. The results showed that, in writing ‘Han’ characters, the errors mostly made by the learners are those related to morphology and syntax. Most of these errors are local ones so they don’t create misuderstanding. Besides, the global errors are also dominant. The factor influencing these errors is the one related to the learners’ mother tongue, Indonesian language or interlanguage errors.Keywords: Chinese language, error analysis, interlanguage errors.